Autoritarismi e immaginari (Altre Modernità, 2013)
(Leonoardo Senkman - Saúl Sosnowski, Fascismo y nazismo en las letras argentinas, Ediciones Lumiere, Buenos Aires, 2009, 183 pp., ISBN 978-987-603- 060-1)di Ilaria Magnani